Estradiol promotes EMT in endometriosis via MALAT1/miR200s sponge function. Issue 2 (February 2019) - Du, Yu; Zhang, Zhibing; Xiong, Wenqian; Li, Na; Liu, Hengwei; He, Haitang; Li, Qi; Liu, Yi; Zhang, Ling
Abstract : Endometriosis is an estrogen-dependent benign gynecological disease that shares some common features of malignancy. Epithelial–mesenchymal transition (EMT) has been recognized as a core mechanism of endometriosis. MALAT1 is widely known as EMT promoter, while miR200 family members (miR200s) are considered as EMT inhibitors. Previous studies have reported that MALAT1 upregulation and miR200s downregulation are observed in endometriosis. MiR200c has been regarded as the strongest member of miR200s to interact with MALAT1. However, whether MALAT1/miR200c regulates EMT remains largely unclear. In this study, the roles of miR200s and MALAT1 in ectopic endometrium were investigated. Additionally, the effects of E2 on EMT and MALAT1/miR200s were examined in both EECs and Ishikawa cells. Notably, E2 could upregulate MALAT1 and downregulate miR200s expression levels and induce EMT in EECs and Ishikawa cells. PHTPP, an ERβ antagonist, could reverse the effect of E2 . Overexpression of miR200c and knockdown of MALAT1 significantly inhibited E2 -mediated EMT, suggesting that both miR200c and MALAT1 are involved in the E2 -induced EMT process in endometriosis. In addition, a reciprocal inhibition was found between miR200s and MALAT1. Therefore, the role of MALAT1/miR200c in EMT is influenced by the presence of estrogen during endometriosis development.